Prenatal diagnosis of a familial 9p12 amplification inherited from a father carrier - Chih-Ping Chen; Chen-Yu Chen; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Chen-Chi Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2021)
Objective: We present prenatal diagnosis of a familial 9p12 amplification inherited from a father carrier. Case report: A 38-year-old, gravida 3, para 2, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a heteromorphic variant of chromosome 9 with a 9p12 amplification on G-band preparations, but it was negative on C-band preparations. Cytogenetic analysis of the parents revealed that the phenotypically normal father carried the same euchromatic 9p + polymorphism. Array comparative genomic hybridization analysis on the DNA extracted from the father's blood revealed no genomic imbalance. At 37 weeks of gestation, a healthy 2760-g female baby was delivered with no phenotypic abnormality. She was doing well at age one year during follow-up. Conclusion: Prenatal diagnosis of a 9p + variant can be a euchromatic chromosome variant of a familial 9p12 amplification without phenotypic consequences.